STRATEGI KEPALA SEKOLAH UNTUK MENINGKATKAN KESIAPAN KERJA SISWA DALAM MEMASUKI DUNIA INDUSTRI DI SMKS AT-THOAT TOROH - Danang Bagus Febryanto; Rasiman Rasiman; Endang Wuryandini (Universitas Sebelas Maret, 2024)
This research aims to analyze the principal's strategy in increasing student work readiness at At-Thoat Toroh Vocational School in order to meet the demands of the industrial world. The background to this research is based on the need for printing graduates who have skills in accordance with industry needs, as well as the obstacles they face.The research method used is a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation and documentation. involving school principals, teachers and students as the main informants to obtain a comprehensive view of policies and implementation of work readiness programs in schools. Data analysis was carried out using content analysis techniques to obtain an overview of the principal's strategies in the context of increasing student work readiness.The research results show that the principal of At-Thoat Toroh Vocational School has implemented several policy strategies such as developing an industrial competency-based curriculum, efforts to involve the Professional Certification Institute (LSP) in the certification process, and developing training and internship programs for teachers. However, the implementation of this policy still faces obstacles.The conclusions of this research emphasize the importance of structured and sustainable strategies to improve student work readiness at At-Thoat Toroh Vocational School. School principals need to strengthen collaboration with industry, encourage nationally recognized competency certification, and expand training programs for teachers to ensure the relevance of teaching to the needs of the world of work.